2016
DOI: 10.3389/fmars.2016.00226
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Impact of Saharan Dust and Polluted Aerosols on Microbial Populations in the East Mediterranean Sea, an Overview of a Mesocosm Experimental Approach

Abstract: Recent estimates of nutrient budgets for the Eastern Mediterranean Sea (EMS) indicate that atmospheric aerosols play a significant role as suppliers of macro-and micro-nutrients to its Low Nutrient Low Chlorophyll water. Here we present the first mesocosm experimental study that examines the overall response of the oligotrophic EMS surface mixed layer (Cretan Sea, May 2012) to two different types of natural aerosol additions, "pure" Saharan dust (SD, 1.6 mg l −1 ) and mixed aerosols (A-polluted and desert orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
79
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(94 citation statements)
references
References 102 publications
(135 reference statements)
13
79
1
1
Order By: Relevance
“…Thanks are also due to George Piperakis for his technical assistance throughout the experiment, Nafsika Papageorgiou for measuring chlorophyll a concentration, Manolis Tsapakis for measuring dissolved nutrient concentration, Christos Panagiotopoulos and Kalliopi Violaki for measuring dissolved organic carbon concentration, and Elisabet Laia Sá Lago for her valuable recommendations regarding the viral reduction approach. Nutrient leaching experiments were conducted in the Israel Oceanographic and Limnological Research (Haifa) and at the University of Leeds, and results are published in Herut et al (2016). Finally, three reviewers are gratefully acknowledged for their valuable comments that largely improved the quality of the manuscript.…”
Section: Author Contributionsmentioning
confidence: 99%
“…Thanks are also due to George Piperakis for his technical assistance throughout the experiment, Nafsika Papageorgiou for measuring chlorophyll a concentration, Manolis Tsapakis for measuring dissolved nutrient concentration, Christos Panagiotopoulos and Kalliopi Violaki for measuring dissolved organic carbon concentration, and Elisabet Laia Sá Lago for her valuable recommendations regarding the viral reduction approach. Nutrient leaching experiments were conducted in the Israel Oceanographic and Limnological Research (Haifa) and at the University of Leeds, and results are published in Herut et al (2016). Finally, three reviewers are gratefully acknowledged for their valuable comments that largely improved the quality of the manuscript.…”
Section: Author Contributionsmentioning
confidence: 99%
“…Our data showed that, although increased food availability was not true, the feeding performance of the dominant copepod C. furcatus did have a response to the atmospheric deposition, through the changes mediated in the microbial food web (Tsagaraki et al, this issue;Herut et al, 2016). This is of great importance for the coupling between lower and higher trophic levels, through a more efficient transfer of food toward top consumers.…”
Section: Discussionmentioning
confidence: 69%
“…A more detailed description of the mesocosm set up and experimental design is provided by Tsagaraki et al (this issue) and Herut et al (2016). For the copepod feeding and production experiments, we used all three treatments (C, SD, and A).…”
Section: Mesocosm Set Up and Experimental Designmentioning
confidence: 99%
“…To further investigate this phenomenon, the MESOAQUA experiment (May 2012; Heraklion, Crete) simulated intense dry atmospheric deposition in the ultraoligotrophic EMS by spiking surface seawater mesocosms (Cretan Sea) with two different natural aerosols collected in the Levantine Basin: Saharan dust (SD) or mixed aerosols (A; Herut et al, 2016). Biogeochemical responses to the addition of SD or A, including plankton community composition and production, pigment concentration, and cycling of macro-nutrients and trace elements, were compared in triplicate to unamended control mesocosms over a period of 8 days (Guo et al, 2016;Herut et al, 2016;Rahav et al, 2016;Tsiola et al, 2016;Tsagaraki et al, under revision, this SI).…”
Section: Abstract: Diacylglycerol Lipids Fatty Acids Oligotrophic Fmentioning
confidence: 99%
“…Biogeochemical responses to the addition of SD or A, including plankton community composition and production, pigment concentration, and cycling of macro-nutrients and trace elements, were compared in triplicate to unamended control mesocosms over a period of 8 days (Guo et al, 2016;Herut et al, 2016;Rahav et al, 2016;Tsiola et al, 2016;Tsagaraki et al, under revision, this SI). In addition to these bulk biogeochemical measures of food web dynamics, the diversity of algal and bacterial cell membrane lipids provides a moderate level of taxonomic and physiological information (e.g., Sato, 1992;Guschina and Harwood, 2006;Sohlenkamp and Geiger, 2015) that can be applied to assess organic matter reactivity (Harvey and Macko, 1997;Wakeham et al, 1997), plankton communities in the ocean (e.g., Van Mooy and Fredricks, 2010), and carbon and nutrient fluxes in marine food webs (Dalsgaard et al, 2003;Sebastián et al, 2016).…”
Section: Abstract: Diacylglycerol Lipids Fatty Acids Oligotrophic Fmentioning
confidence: 99%